Comparative Transcriptome Analyses of Resistant and Susceptible Near-Isogenic Wheat Lines following Inoculation with Blumeria graminis f. sp. tritici. (2nd May 2017) - Xing, Piyi; Zhang, Xueying; Bao, Yinguang; Wang, Yuhai; Wang, Honggang; Li, Xingfeng
Abstract : Powdery mildew is one of the most important diseases of wheat. In this study, the leaf RNA samples of wheat NILs carrying powdery mildew resistant and susceptible Pm2 alleles (L031 and Chancellor) and its F1 hybrid at two time points (16 h and 96 h postinoculation) were used for RNA-seq analysis. We carry comparison between similar materials at different times and between different materials at same times. The overlapping DEGs between the dominant phenotypes (L031 and F1 hybrid) and the recessive phenotype (Chancellor) were 1028 and 2214 DEGs, which were clearly lower than those between the dominant and recessive parents and thus could provide relatively accurate and valuable information. GO and KEGG enrichment analysis of DEGs revealed that other than the expected defense-related genes, differential up- and downregulation of genes from many other signaling networks were also involved. Comparative transcriptome analysis also revealed that early-stage postinoculation is important and suitable time points to study expression profiles and signaling pathways of resistance-related genes following fungal inoculation. qRT-PCR analyses showed highly consistent expression patterns of genes with RNA-seq data. The results will aid in the identification of genes and signaling pathways involved in powdery mildew response in wheat.